DESIGN, FORMULATION, AND EVALUATION OF SOLID DISPERSION TABLETS OF POORLY WATER-SOLUBLE ANTIDIABETIC DRUG USING NATURAL POLYMER - SUDIPTA DAS; PRIYANKA MANDAL (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the present study was to formulate the solid dispersion (SD) of poorly water-soluble drug glimepiride and the development of the tablets of prepared SD of glimepiride using natural and synthetic polymers. Methods: The SD of glimepiride was to prepare using fusion method. The tablets were prepared by wet granulation method using synthetic polymer such as HPMC and natural polymer gellan gum. Results: The granules were evaluated by determining the angle of repose (23.70±0.761 to 29.21±0.127º), bulk density, tapped density, Hausner ratio, and Carr’s index. It shows satisfactory results. The tablets were subjected to the measurement of hardness (3.9±0.08 to 4.6±0.04kg/cm2), friability (0.22±0.004 to 0.40±0.005%), and in vitro release studied. Release study of pure drug was performed. In the release study, SD of glimepiride tablets with gellan gum gives considerably good result compared to HPMC. Conclusion: From the results, it was shown that dissolution rate of pure glimepiride was very slow. When the glimepiride was prepared in SD form, then the dissolution rate was very fast. The tablets of the SD of glimepiride were prepared and release study was shown depending on various quantities of HPMC and gellan gum used. Therefore, the long term stability study is required for future development of this formulation.